2012
DOI: 10.3390/s120506695
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of Indoor Places Using the Kinect Sensor

Abstract: The categorization of places in indoor environments is an important capability for service robots working and interacting with humans. In this paper we present a method to categorize different areas in indoor environments using a mobile robot equipped with a Kinect camera. Our approach transforms depth and grey scale images taken at each place into histograms of local binary patterns (LBPs) whose dimensionality is further reduced following a uniform criterion. The histograms are then combined into a single fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 28 publications
(31 reference statements)
0
38
0
1
Order By: Relevance
“…Our work is close to [20], where a Kinect camera is used to categorize pairs of depth and gray scale images into indoor places using histograms of local binary patterns. However, the working range of the Kinect camera is very short.…”
Section: Related Workmentioning
confidence: 99%
“…Our work is close to [20], where a Kinect camera is used to categorize pairs of depth and gray scale images into indoor places using histograms of local binary patterns. However, the working range of the Kinect camera is very short.…”
Section: Related Workmentioning
confidence: 99%
“…Using the multi-class SVM on features extracted from real 3D data, Swadzba and Wachsmuth [23] achieved approximately 80% accuracy, while the work of Mozos et al [24] showed accuracies above 92% and we have obtained approximately 97% [25]. It is to be noted that the accuracies mentioned here are achieved by different methods, on different data sets and may address completely different tasks.…”
Section: Introductionmentioning
confidence: 88%
“…In a similar setup, we implemented both binary and multi-class logistic regression based solutions, and have been able to achieve accuracies above 98% [21,22]. In recent years, SVM as a prominent classifier, has been gaining popularity over other approaches in many applications [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…В этом направлении ведется разработка специализированных языков для описания среды, алгоритмов построения семантических моделей на основании данных сенсоров, создаются специализированные базы семантической информации, [1], [2], [3]. Однако в настоящее время, несмотря на значительные усилия, предпринимаемые мировыми производителями, на рынке практически нет роботов, которые использовали бы семантическую информацию для построения целенаправленного поведения.…”
Section: Introductionunclassified